Measuring Tom and Tol Elasticity in Forced Sales Auctions: Lessons Learned from Indonesia - Triono, Doni; Nurbiyanto, Nurbiyanto; Prabowo, Sakti; Raffiwan, Andi (Dinasti International Journal of Economics, Finance & Accounting, 2025)
While many studies have explored the relationship between time-on-the-market (TOM) and price, few have looked at time-on-the-liquidation (TOL). This study measures TOM and TOL elasticity in real estate auctions, analyzing data from 12 State Assets and Auction Service Offices between 2021 and mid-2023 using convenience sampling. The results show TOM elasticity for forced sales is elt=1, while TOL elasticity is elt=0. TOM elasticity responds to price changes, but TOL does not. Lower auction prices affect TOM elasticity, but not TOL. To make TOL elasticity dynamic, regulatory changes allowing for flexible TOL could be introduced.